2022
DOI: 10.1111/jgh.15835
|View full text |Cite
|
Sign up to set email alerts
|

Changes in halitosis value before and after Helicobacter pylori eradication: A single‐institutional prospective study

Abstract: Background and Aim Although patients report either improved or worsened halitosis after Helicobacter pylori eradication therapy, such complaints are subjective. Only a few studies have objectively evaluated reports of changes in halitosis after H. pylori eradication; thus, this study aimed to investigate these changes after a successful H. pylori eradication. Methods Between February 2015 and October 2018, 56 347 patients visited the clinic. Informed consent for participation in this study was obtained from 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…[63] Most patients with malodor experience an improvement in halitosis after eradicating H pylori. [35,[64][65][66] H pylori contributes to halitosis by generating hydrogen sulfide and methyl mercaptan. [67] The alterations in the mucosa of the gastric region, characterized by erosive changes, are strongly linked to elevated levels of VSC, indicating that halitosis might stem from damage to the GI mucosa caused by H pylori.…”
Section: Discussionmentioning
confidence: 99%
“…[63] Most patients with malodor experience an improvement in halitosis after eradicating H pylori. [35,[64][65][66] H pylori contributes to halitosis by generating hydrogen sulfide and methyl mercaptan. [67] The alterations in the mucosa of the gastric region, characterized by erosive changes, are strongly linked to elevated levels of VSC, indicating that halitosis might stem from damage to the GI mucosa caused by H pylori.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 The relationship between H. pylori and halitosis was first proposed by Marshall et al 15 Since then, a growing number of studies support this theory by proving that halitosis is reduced after H. pylori eradication. 18 A meta-analysis with the highest level of evidencebased medicine published in 2016 provided clear evidence that H. pylori infection correlated with halitosis, and H. pylori eradication therapy might be helpful in those patients with refractory halitosis. 20 Based on this theory and successful experience in literature, a large number of patients with extraoral halitosis and good oral hygiene status have been referred to our gastrointestinal clinic by dentists.…”
Section: Discussionmentioning
confidence: 99%
“…A possible link between H. pylori and halitosis was noted about three decades ago 15,16 . Since then, a number of studies have demonstrated the relationship between halitosis and H. pylori by demonstrating improvement of halitosis after successful eradication therapy 17,18 . Lee et al 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, left unchecked, chronic oral inflammation may advance to gum disease, and is linked to several conditions beyond the oral cavity, including diabetes, cardiovascular diseases, and Alzheimer’s disease [28] , [29] , [30] , [31] , [32] . Similarly, chronic halitosis is associated with Helicobacter pylori infections, liver disease, and gastroesophageal reflux disease [33] , [34] , [35] . Bi-directional associations like these are opportunities for health professionals to act on findings from early risk assessments and encourage proactive healthcare measures [36] .…”
Section: Introductionmentioning
confidence: 99%